Elucidating the Performance Limitations of Alkaline Electrolyte Membrane Electrolysis: Dominance of Anion Concentration in Membrane Electrode Assembly. Issue 19 (18th August 2020) - Razmjooei, Fatemeh; Farooqui, Azharuddin; Reissner, Regine; Gago, Aldo Saul; Ansar, Syed Asif; Friedrich, Kaspar Andreas
Abstract: Anion exchange membrane water electrolyzers (AEMWEs) offer a cost‐effective technology for producing green hydrogen. Here, an AEMWE with atmospheric plasma spray non‐precious metal electrodes was tested in 0.1 to 1.0 M KOH solution, correlating performance with KOH concentration systematically. The highest cell performance was achieved at 1.0 M KOH (ca. 0.4 A cm −2 at 1.80 V), which was close to a traditional alkaline electrolysis cell with ≈6.0 M KOH. The cell exhibited 0.13 V improvement in the performance in 0.30 M KOH compared with 0.10 M KOH at 0.5 A cm −2 . However, this improvement becomes more limited when further increasing the KOH concentration. Electrochemical impedance and numerical simulation results show that the ohmic resistance from the membrane was the most notable limiting factor to operate in low KOH concentration and the most sensitive to the changes in KOH concentration at 0.5 A cm −2 . It is suggested that the effect of activation loss is more dominant at lower current densities; however, the ohmic loss is the most limiting factor at higher current densities, which is a current range of interest for industrial applications. Abstract : Dominant side : Highly efficient anion exchange membrane water electrolysis using non‐noble metal electrodes fabricated through a plasma spray technique is presented and the cell performance is correlated with KOH concentration of the electrolyte using both experimental and simulation analysis.